Faktor penentu amalan kitar semula generasi y di Terengganu - Ibrahim, Mamat; Che Ku Noor Haniza, Che Ku Hitam; Mohd Yusri, Ibrahim (2017)
Recycling campaign in Malaysia has failed because the practice of recycling among residents is still low. Thus, the Ministry of Housing and Local Government Malaysia has relaunched the campaign in 2001. Despite the high potential of recycling, only 10 per cent the amount of waste being recycled. This rate increased slowly, an increase of 5 percent over the past 12 years. This study aimed to investigate the relationship and the contribution of attitude towards recycle, environmental concerns and recycling practiced by Y generation in Terengganu. The respondents consisted of 338 students from seven institutions of higher education that represents Y generation for each district in the State. Questionnaire on environmental attitudes, environmental concerns and recycling practices was modified from previous studies and used as a research tool. Data were analyzed using SPSS 20. The findings showed that there was a significant relationship between the attitudes towards environment and practice of recycling (r = 0.80, sig = 0.00) and environmental concerns with the practice of recycling (r = 0.82, sig = 0.00). The findings also discovered that the environmental attitudes and the concern for the environment have contributed 72.2% to the practice of recycling. This study suggests a number of strategies to increase recycling practices.